2008
DOI: 10.1007/s11469-008-9155-3
|View full text |Cite
|
Sign up to set email alerts
|

An Appraisal of the Impact of the Depiction of Gambling in Society on Youth

Abstract: Youth are currently growing up in a culture where gambling is legal, accessible and widely supported. Although minors are largely restricted from regulated gambling, the greater incidence of problem gambling amongst youth than adults suggests that the perception of gambling as a harmless entertainment activity is inaccurate. Gambling is widely portrayed in the media often in an inaccurate or exaggerated way that normalizes gambling and may encourage youth to participate. Wagering on sporting events is becoming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…At the very least, the development of responsible codes of practice and guidelines should be established (Monaghan and Derevensky 2008;Monagahan et al 2008). While many jurisdictions have endorsed such responsible codes of advertising, the enforcement of such codes is absent by regulatory boards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the very least, the development of responsible codes of practice and guidelines should be established (Monaghan and Derevensky 2008;Monagahan et al 2008). While many jurisdictions have endorsed such responsible codes of advertising, the enforcement of such codes is absent by regulatory boards.…”
Section: Discussionmentioning
confidence: 99%
“…While there is a paucity of research examining the potential effects of gambling advertisements on children and adolescents behavior (Monaghan and Derevensky 2008;Youn et al 2000), it is widely accepted that the media has a powerful impact upon people's behaviors and attitudes (De Pelsmacker et al 2002;Feeney 2004;Wiseman et al 2005). An abundance of research has demonstrated the impact of alcohol advertisements upon youth drinking behaviors and intentions.…”
mentioning
confidence: 99%
“…The use of social casino games among young people is of particular concern as this population is at greatest risk for the development of gambling problems (Monaghan & Derevensky, 2008). Several studies of adolescents and young adults have found that those who play social casino games online are also more likely to engage in gambling, and are at greater risk of experiencing significant gambling-related problems (Forrest, McHale, & Parke, 2009;King et al, 2012;McBride & Derevensky, 2012;Mihaylova & Kairouz, 2010).…”
Section: Problem Gamblingmentioning
confidence: 99%
“…Ladouceur [132] 1996 Canada To review the prevalence of problem or pathological gambling in children, adolescents and adults in Canada J Gamb Stud Monaghan and Derevensky [133] 2008 Australia To appraise the impact of the depiction of gambling in society on youth. Int J Ment Health Addict Monaghan et al [134] 2008 Australia To examine the current marketing techniques used to promote gambling and how they affect youth J Gamb Issues Selekman [135] 2008 U.S. To determine if gambling is normal adolescent behavior or pathological addiction J Pediatr Nurs Shaffer and Hall [1] 1996 U.S. To conduct a meta-analytical review of nine studies on gambling among adolescents in Canada and the United States.…”
Section: J Gamb Behavmentioning
confidence: 99%